Is inclusive business for you? Managing and upscaling an inclusive company: Lessons from the field - Sopov, Monika; Saavedra, Yeray; Sertse, Yared; Vellema, Wytse; Verjans, Henric (CTA / The Seas of Change initiative / WUR, 2014)
Presented in an attractive and accessible way, this publication provides readers with a valuable understanding of how agri-food markets can contribute to food security and rural poverty reduction, while still building profitable commercial relations. It aims to distil original research on incentives and mechanisms for inclusiveness, success factors and obstacles, and opportunities for scaling up successful models. Bringing together ten case studies across a wide range of commodities in East Africa, the book features numerous photos, tables and diagrams, and includes a useful ‘Lessons learnt’ chapter at the end.